Overall job satisfaction among academic staff of the MARA Institute of Technology, Shah Alam / Mohamed Hashim Mohd. Kamil - Mohd. Kamil, Mohamed Hashim (Biro Penyelidikan dan Perundingan, Institut Teknologi MARA, 1994)
The major focus of this study was 1o examine whether overall job satisfaction can be better predicted when placed within the context of the individual's total life situation. The main objective of the study was to determine factors that contribute towards job satisfaction among academic staff of the MARA Institute of Technology (ITM), Shah Alam. Specifically, it attempted to ascertain whether selected individual attributes, selected jobrelated variables, and selected non-job related variables are potential determinants of overall of satisfaction.